TWOFER: USING CDA IN THE CLASSROOM FOR ENHANCING STUDENTS LANGUAGE SKILLS AND CRITICAL THINKING - Istiqlaliah Nurul Hidayati (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
ABSTRACT Nowadays, through technology, information spreads very rapidly. When something happens in one place, in a second it can be known by other people in other faraway places. Unfortunately the information is not always true. Many irresponsible people create misleading information and spread it massively which is known as hoax. This misleading information can provoke many bad effects even sometimes it is dangerous. The hoax can contain hatred, false health information, untrue disaster warning, and so on. This phenomena cannot be ignored. There have been many victims. To protect people from hoax can be done by training their critical thinking ability. One of the ways to make people able to think critically is through the implementation of critical discourse analysis (CDA). This research is aimed at building students’ critical thinking and also improving their English skills through the use of CDA. The method employed in this study was action research which was also completed by a focused group discussion. The research result shows that the students could improve their English skills and became more critical in writing a response to a text given by the lecturer by analyzing the text using the principles of CDA, not merely relying on their own opinion. Keywords: Critical Discourse Analysis; Critical Thinking Ability; English Language Skills